2020
DOI: 10.1016/j.icarus.2020.113660
|View full text |Cite
|
Sign up to set email alerts
|

Europa’s surface water ice crystallinity: Discrepancy between observations and thermophysical and particle flux modeling

Abstract: Physical processing of Europan surface water ice by thermal relaxation, charged particle bombardment, and possible cryovolcanic activity can alter the percentage of the crystalline form of water ice compared to that of the amorphous form of water ice (the "crystallinity") on Europa's surface. The timescales over which amorphous water ice is thermally transformed to crystalline water ice at Europan surface temperatures (80-130 K) suggests that the water ice there should be primarily in the crystalline form, how… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 50 publications
4
7
0
Order By: Relevance
“…We estimated a crystallinity of ∼15% based on the crystalline and amorphous water-ice abundances in the 17e009 NIMS cube (Figure 17). This was slightly lower than, but still consistent with, spectroscopically derived crystallinities of ∼30% for the full-disk leading hemisphere, which is dominated by warmer (and therefore more crystalline), lower-latitude locations (Berdis et al 2020). As discussed previously, Adonis Linea crosses the NIMS observation at ∼124°-125°W.…”
Section: Derived Properties Near the South Polesupporting
confidence: 80%
See 2 more Smart Citations
“…We estimated a crystallinity of ∼15% based on the crystalline and amorphous water-ice abundances in the 17e009 NIMS cube (Figure 17). This was slightly lower than, but still consistent with, spectroscopically derived crystallinities of ∼30% for the full-disk leading hemisphere, which is dominated by warmer (and therefore more crystalline), lower-latitude locations (Berdis et al 2020). As discussed previously, Adonis Linea crosses the NIMS observation at ∼124°-125°W.…”
Section: Derived Properties Near the South Polesupporting
confidence: 80%
“…A lower crystallinity near the pole is expected owing to (1) colder temperatures, which indicates a longer amount of time for the amorphous water-ice to crystallize (Kouchi et al 1994;Jenniskens et al 1998;Mastrapa et al 2013), and (2) migration of amorphous plume material (Kouchi et al 1994;Hansen & McCord 2004). These crystallinities are in agreement with those derived using full-disk ground-based spectroscopic observations of Europa's leading hemisphere and laboratory-produced crystalline and amorphous water-ice (Berdis et al 2020). They found that the spectroscopically derived crystallinity of Europa's full-disk leading hemisphere is ∼27%-36%, whereas the crystallinity derived from thermophysical modeling and particle flux is ∼80%-95%.…”
Section: Location Comparison Of Composition and Crystallinitysupporting
confidence: 78%
See 1 more Smart Citation
“…(1) The surface of Enceladus is dominated by the same hexagonal ice I h as used in our experiments (Filacchione et al, 2007, 2010). (2) The surface of Europa may contain a small fraction of amorphous ice due to irradiation effects, but it appears nevertheless dominated by ice I h (Berdis et al, 2020; Hansen & McCord, 2000). (3) Low H 2 O vapor pressure and airless conditions at the surface of Europa and Enceladus would ease release and escape of H 2 O, which suggests that ice could redistribute less efficiently within plume deposits than in our experiments.…”
Section: Implications For Strength Of Surface Plume Deposits On Enceladus and Europamentioning
confidence: 99%
“…As a result, layered structures, from outermost ice Ih to inner high-pressure ices, were formed. Although the temperature of the icy satellite’s surface differs among each satellite and between equatorial and polar regions (e.g., Berdis et al, 2020 ), we will discuss using average temperatures for simplicity. We assume that the surface temperatures of icy satellites of Jupiter, Saturn, and Uranus are 110, 85, and 65 K, respectively.…”
Section: Discussionmentioning
confidence: 99%